2020
DOI: 10.35219/foodtechnology.2020.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial activities of hydrophilic extracts from shallot and garlic bulbs, and their effects on round scad during iced storage

Abstract: The present study aimed to investigate the in vitro antioxidant and antimicrobial activities of hydrophilic extracts prepared from shallot and garlic bulbs, and their effects on round scad during iced storage. Both the shallot and garlic extracts exhibited antioxidant activity concerning DPPH radical scavenging, total reducing power, and lipid peroxidation inhibition. The extracts also had antimicrobial activity against both Gram-positive (Bacillus cereus, Staphylococcus aureus) and Gramnegative (Escherichia c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…It was found that shallot extract exhibited good antioxidant activity concerning DPPH radical scavenging, total reducing power, and lipid peroxidation inhibition. Round scad treated with either shallot or garlic extracts kept their natural sensory characteristics accepted for food-grade longer than 4 days of ice storage, compared with the control (without treatment) ( Figure 2k ) ( 19 ). A recent study reported the development of active packaging film using sodium alginate and carboxymethyl cellulose along with shallot waste extract.…”
Section: Antioxidant and Anti-inflammatory Activitymentioning
confidence: 98%
See 2 more Smart Citations
“…It was found that shallot extract exhibited good antioxidant activity concerning DPPH radical scavenging, total reducing power, and lipid peroxidation inhibition. Round scad treated with either shallot or garlic extracts kept their natural sensory characteristics accepted for food-grade longer than 4 days of ice storage, compared with the control (without treatment) ( Figure 2k ) ( 19 ). A recent study reported the development of active packaging film using sodium alginate and carboxymethyl cellulose along with shallot waste extract.…”
Section: Antioxidant and Anti-inflammatory Activitymentioning
confidence: 98%
“…(k) Apparent changes occurred in round scad during ice storage. Shallot extract, the round scad was immersed in shallot extract; Garlic extract, the round scad was immersed in garlic extract; Control, the round scad was immersed in distilled water ( 19 , 46 ). (l) Anti-angiogenic effect of ethyl acetate fraction on CAM model of angiogenesis (arrows show neovascular forming in the chicken chorioallantoic membrane); (A) control, (B) treatment with EA fraction at 3 ng/egg, (C) treatment with ethyl acetate fraction at 10 ng/egg ( 47 ).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation